2018
DOI: 10.1049/iet-rpg.2017.0859
|View full text |Cite
|
Sign up to set email alerts
|

Shifting air‐conditioner load in residential buildings: benefits for low‐carbon integrated power grids

Abstract: This study presents a simulation of low-carbon electricity supply for Australia, contributing new knowledge by demonstrating the benefits of load shifting in residential buildings for downsizing renewable electricity grids comprising wind, hydro, biomass, and solar resources. The load-shifting potential for the whole of Australia is estimated, based on air-conditioner load data and an insulation model for residential buildings. Load shifting is applied to enable transferring residential airconditioner load fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…We have obtained a high installed capacity and low capacity factor in our study compared with Ali et al This is because the shiftable air‐conditioner load in their study accounts for around 4% of total electricity demand compared with a shiftable EWH load of around 1.4% of total demand. The opportunities to reduce the capacity of renewable electricity grid increase with an increase in the amount of shiftable load provided that the spilt electricity is not drained out.…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…We have obtained a high installed capacity and low capacity factor in our study compared with Ali et al This is because the shiftable air‐conditioner load in their study accounts for around 4% of total electricity demand compared with a shiftable EWH load of around 1.4% of total demand. The opportunities to reduce the capacity of renewable electricity grid increase with an increase in the amount of shiftable load provided that the spilt electricity is not drained out.…”
Section: Resultsmentioning
confidence: 45%
“…This section presents a comparison between the results obtained from our simulation and previous studies done by Ali et al 4 and Lenzen et al 1 We run our simulation with the same input parameters (Table 1) and a biofuel capacity limited to 15-folds the existing capacity (1.7 GW) as observed in the previous studies. 21,39,40 We run our simulation with the load-shifting algorithm and allow a 1-hour shift in EWH load to reduce the installed capacity of the renewable electricity grid; a similar approach is explored by Ali et al 4 (Table 4), we have demonstrated that by shifting EWH demand, the capacity factor of 100%-renewable electricity grid can be increased and the total capacity of the grid can be decreased.…”
Section: Comparison With Previous Studies For Australiamentioning
confidence: 98%
See 2 more Smart Citations
“…Our load-shifting algorithm is based on the work of Ali et al (2018), Ali et al (2019), and Keck et al (2019). Our concept of using the demand of seawater desalination for load-shifting has the following additional key benefits:…”
Section: The Load-shifting Algorithmmentioning
confidence: 99%